Four Ways of Aggregating Monies - Pesek, B. P. (Journal of Financial and Quantitative Analysis, 1972)
Aggregation of monies must be determined in accord with the theory using the aggregate. This theory must specify aggregation (1) eligibility rules and (2) weights. Four current methods are evaluated on this basis: Fisher's aggregation bases eligibility on significant quantities Vi of monies Mi and attaches quantity weights Vi/Vn (Vn being numeraire). Pesek-Saving aggregation merely substitutes social marginal value weights Vipi/Vnpn. Friedman-Schwartz aggregation has eligibility depend on good subsequent statistical performance and uses weights given by private marginal values (gross of subsidies). Chetty's aggregation has all assets eligible and weighted by cross-elasticities of demand.